PENGARUH PENGGUNAAN METODE DISKUSI, MEDIA PEMBELAJARAN DAN LINGKUNGAN TERHADAP HASIL BELAJAR SISWA KELAS VII MATA PELAJARAN IPS TERPADU PADA SMP NEGERI 22 BANDAR LAMPUNG TAHUN AJARAN 2011/2012 - Vincencius Eko Toto Raharjo; Yon Rizal; Samsi Samsi (JEE (Jurnal Edukasi Ekobis), 2013)
This research is aimed to know about the influence of using the discussion method, media and learning environment for student learning outcomes of VII Grade, especially in IPS Terpadu class at SMP Negeri 22 of Bandar Lampung in Academic Year 2011/2012. The people in this research are all students of VII grade at SMP Negeri 22 of Bandar Lampung in Academic Year 2011/2012, where 188 students are spread in 6 classes. Sampling was done by using simple random sampling, where 128 of students were getting by Slovin Formula. The method that used in this research is descriptive research with approach of ex post facto and surveys. To test the three of hypothesis, it was using simple linear regression, but for the fourth hypothesis, it was using multiple linear regressions. The analysis revealed: (1) There is influence of the use of the discussion on learning outcomes of students of VII grade in IPS Terpadu class at SMP Negeri 22 of Bandar Lampung in Academic Year 2011/2012. (2) There is influence of the use of instructional media on learning outcomes of students of VII grade in IPS Terpadu class at SMP Negeri 22 of Bandar Lampung in Academic Year 2011/2012. (3) There is influence of environment on learning outcomes of students of VII grade in IPS Terpadu class at SMP Negeri 22 of Bandar Lampung in Academic Year 2011/2012. (4) There is influence of the use of the discussion method, instructional media, and the environment on learning outcomes of students of VII grade in IPS Terpadu class at SMP Negeri 22 of Bandar Lampung in Academic Year 2011/2012.